The mode of action of the acyl-diethylamide molluscicides - Solomon, Keith Ross (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1971)
From Introduction: That bilharziasis an important public health, social and economic problem in the tropical and subtropical countries of the world is well appreciated. (WHO, 1965) Bilharsiasis is the disease caused by parasitic worms of the genus Schistosoma having certain fresh water snails as the intermediate host. In South Africa the more important snails are Bulinus africanus and B. globosus, the secondary hosts of Schistosom haematobium. (WHO, 1965) One method of controling the disease is to reduce the numbers of the intermediate host snails to such a low level that transmission cannot occur (WHO, 1965 and Macdonald, 1965) This has led to a strong interest in those substances that kill snails. The first recorded use of a molluscicide, copper sulphate, was during the first world War in Egypt. (De Villiers, 1965) More recently, the more or less random testing of large numbers of compounds led to the discovery of a large number of molluscicides. These were the heavy metal compounds such as the salts of mercury and arsenic, the substituted phenols such as pentachlorophenol (PCP) and the 2-substituted 4:6-dinitrophenols. (De Villiers, 1965) These compounds are good molluscicides but suffer from a number of disadvantages. The use of copper compounds in hard waters is impractical as the copper precipitates out as the less effective carbonate. The heavy metal salts are expensive and biocidal thus making the treated water unsuitable for human or agricultural use. The phenolic compounds are unpleasant and dangerous to handle and the hydrolysis of PCP is catalysed by sunlight in clear waters. High concentrations of these compounds are required, thus increasing transport and handling costs, particularly in inaccessible areas.
Keywords: Pesticides; Molluscicides